Kegiatan Pelatihan Seni Hadrah sebagai Upaya Penguatan Karakter Religius Remaja di Masjid Kauman Gedongan Waru Sidoarjo - Muhammad Athour Rohman (Lembaga Pengembangan Kinerja Dosen, 2026)
Religious culture that is still quite strong in the community is an important capital in the implementation of youth development programs. However, the influence of social media, promiscuity, and the lack of religious activities that are attractive to the younger generation have led to a decrease in adolescents' interest in religious activities in mosques. Therefore, this research aims to form the character of discipline, responsibility, and cooperation in the group through Islamic hadrah art activities. This study uses the Asset Based Community Development (ABCD) method, which is a community empowerment approach that focuses on the strengths and potentials possessed by the community, not on existing shortcomings or problems. In this approach, the community is invited to identify various assets they have, such as human resources, local institutions, cultural values, and social networks that can be used to overcome the problems they face. The results of the study showed that the adolescent participants experienced improved skills in playing hadrah and understanding of religious values. In addition, there has been a change in behavior towards being more disciplined, active, and caring for religious activities in the mosque environment.